Discrepancy Between Forceps Biopsy and Resection in Colorectal Polyps: A 1686 Paired Screening-Therapeutic Colonoscopic Finding - Jiang Y; Wang J; Chen Y; Sun H; Dong Z; Xu S (Therapeutics and Clinical Risk Management, 2022)
Yuanxi Jiang, Junwen Wang, Ying Chen, Huihui Sun, Zhiyu Dong, Shuchang Xu Department of Gastroenterology, Tongji Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Shuchang Xu; Zhiyu Dong, Department of Gastroenterology, Tongji Hospital, Tongji University School of Medicine, No. 389, Xincun Road, Putuo District, Shanghai, People’s Republic of China, Tel +86-136 0199 9711, Email xsc-students@hotmail.com; 1253292@tongji.edu.cnPurpose: To identify pathology discrepancy between forceps biopsies and polypectomy specimens in colorectal polyps, as well as the reliability of biopsy-based treatment strategy.Methods: All endoscopic polypectomy cases with forceps biopsies performed within 6 months were included in the study. The biopsies were compared with polypectomy specimens in terms of concordance of histological diagnosis. A logistic regression model was used to investigate the independent predictors of upgrade in histological diagnosis compared with concordance in histological diagnosis.Results: A total of 1686 paired screening-therapeutic colonoscopies and 1739 paired biopsy-polypectomy specimens were enrolled in the study. The grade of dysplasia in 84.5% of biopsy specimens were concordant to polypectomy specimens, but this proportion decreased to 75.4% when the specimens were classified using tubular or villousness structure. 10.1% and 5.4% of biopsy specimens were upgraded and downgraded in assessing grade of dysplasia, respectively, while 14.3% and 10.3% of biopsy specimens were upgraded and downgraded in assessing tubular or villousness structure, respectively. In subgroup analysis stratified by size of polyps, 9.0% and 10.6% of biopsies obtained from polyps smaller than 10 mm were upgraded in assessing dysplasia and tubular or villousness structure, respectively. This proportion increased to 10.7% and 21.3%, respectively, in biopsies obtained from polyps larger than 10 mm. Larger size of polyps and pedunculated polyps were associated with a higher incidence of upgrade in histological diagnosis. Nearly 25% of biopsy specimens with high-grade dysplasia were identified as adenocarcinoma in polypectomy specimens.Conclusion: The concordance between biopsy and polypectomy specimens is not adequate. The biopsy-based treatment strategy is not reliable and should not be considered as an indicator for further treatment, particularly in large or pedunculated polyps.Keywords: colorectal polyps, colorectal adenoma, colonoscopy, pathology